Community participation in general health initiatives in high and upper-middle income countries: A systematic review exploring the nature of participation, use of theories, contextual drivers and power relations in community participation. (September 2018) - Hoon Chuah, Fiona Leh; Srivastava, Aastha; Singh, Shweta Rajkumar; Haldane, Victoria; Huat Koh, Gerald Choon; Seng, Chia Kee; McCoy, David; Legido-Quigley, Helena
Abstract: Community participation is commonly regarded as pivotal in enabling the success of many health initiatives. However, the theoretical constructs, and evidence about the contextual drivers and relational issues that shape participation is lacking. The aim of this systematic review was to examine the evidence for published academic literature on community participation in relation to general, non-disease specific health initiatives, including the use of theories to inform community participation, and the study of contextual drivers and relational issues that influence community participation, with a focus on high and upper-middle income countries. We searched multiple databases including Medline, Embase, Scopus, LILACs and Global Health from January 2000 to September 2016. We screened papers for inclusion, then conducted data extraction and a narrative synthesis of the data. Only papers that focused on general health were included. Disease-specific literature was excluded. 27, 232 records were identified, with 23, 468 after duplicate removal. 79 papers met our final inclusion criteria. Overall, our findings show that strategies to encourage community participation in health initiatives can be categorized along a continuum that varies from less to more participation and control among the community. Our analysis of reported outcomes demonstrates that community participation in general health initiatives can contribute to positive process, social and health outcomes. Social outcomes are more often associated with increasing community participation in our selection of papers. Overall, our findings reaffirm the understanding that community participation is a complex process that is strongly influenced by the context in which it occurs, and that social factors such as power relations must be carefully considered. There is a need for more robustly designed studies to improve the theorization of community participation, and to draw out a better understanding of how tangible and intangible elements such as power, influence community participation and its outcomes. Highlights: Studies on community participation in general health interventions lack theories. Community participation can yield positive service, social and health outcomes. Social outcomes are more likely reported with increasing community participation. Power relations is a key determinant of community participation. Contextual factors must be considered to ensure successful community participation.